2017
DOI: 10.1007/s11060-017-2618-2
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Pediatric Neuro-Oncology Rating of Treatment Intensity (PNORTI)

Abstract: Measures of treatment intensity for childhood cancer are needed in research in order to control for variability in treatments. Existing measures of treatment intensity for childhood cancers do not reflect the complexities of treatment protocols for central nervous system (CNS) tumors. This paper describes the development of the Pediatric Neuro-Oncology Rating of Treatment Intensity (PNORTI). PNORTI development occurred in three phases. Phase 1: five experts in pediatric neuro-oncology created a 5-point scale o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Post hoc analyses were conducted for survivors of pediatric brain tumors to contextualize the unexpected, crossed interaction between baseline irony and empathy and social skills and peer relationships over time. We examined whether the crossed interactions varied as a function of time‐since‐diagnosis, the intensity of treatment using the Pediatric Neuro‐Oncology Rating of Treatment Intensity (PNORTI) 21 and treatment risk factors using the Neurological Predictor Scale (NPS) 22 . Results showed that the three‐way interaction between time, irony and empathy, and time‐since‐diagnosis was significant ( b = −0.04, se = 0.01, t = − 2.76, P = 0.011), with simple slopes demonstrating an increase in the crossed interaction between time and irony and empathy with an increase in time‐since‐diagnosis.…”
Section: Resultsmentioning
confidence: 99%
“…Post hoc analyses were conducted for survivors of pediatric brain tumors to contextualize the unexpected, crossed interaction between baseline irony and empathy and social skills and peer relationships over time. We examined whether the crossed interactions varied as a function of time‐since‐diagnosis, the intensity of treatment using the Pediatric Neuro‐Oncology Rating of Treatment Intensity (PNORTI) 21 and treatment risk factors using the Neurological Predictor Scale (NPS) 22 . Results showed that the three‐way interaction between time, irony and empathy, and time‐since‐diagnosis was significant ( b = −0.04, se = 0.01, t = − 2.76, P = 0.011), with simple slopes demonstrating an increase in the crossed interaction between time and irony and empathy with an increase in time‐since‐diagnosis.…”
Section: Resultsmentioning
confidence: 99%
“…Post hoc analyses were conducted for the BT group to help contextualize the unexpected, crossed interaction between baseline Irony & Empathy and social skills and peer relationships over time. We examined whether the crossed interactions varied as a function of time-since-diagnosis, the intensity of treatment using the Pediatric Neuro-Oncology Rating of Treatment Intensity (PNORTI) [20] and treatment risk factors using the Neurological Predictor Scale (NPS) [21]. Results showed that the 3-way interaction between time, Irony & Empathy and time-since-diagnosis was significant (b = -0.04, se = 0.01, t = -2.76, p = .011), with simple slopes demonstrating an increase in the crossed interaction between time and Irony & Empathy with an increase in time-since-diagnosis.…”
Section: Post Hoc Analysesmentioning
confidence: 99%
“…Data was collected on the following characteristics: demographic (age at diagnosis, gender, race, ethnicity), clinical (type of cancer and Intensity of Treatment Rating scale (ITR-3) 28 and treatment (RDN NA). Treatment intensity was assigned using ITR-3, a validated, standardized rating scale taking into account types of treatment patient will receive based on diagnosis.…”
Section: Disease-related and Treatment Related Characteristicsmentioning
confidence: 99%
“…The ITR scale has four levels of treatment intensity: 1 (least), 2 (moderately), 3 (very) and 4 (most). 28 Diagnoses were recoded into four categories based on tumor type and treatment: retinoblastoma, neuroblastoma, renal/hepatic tumors, sarcoma/other solid tumors. Age group at diagnosis were < 2 years and [?]…”
Section: Disease-related and Treatment Related Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation